2017
DOI: 10.1590/0102-311x00054016
|View full text |Cite
|
Sign up to set email alerts
|

Uso e necessidade de prótese dentária em idosos brasileiros segundo a Pesquisa Nacional de Saúde Bucal (SBBrasil 2010): prevalências e fatores associados

Abstract: Resumo: O objetivo deste estudo foi avaliar o uso e a necessidade de prótese dentária entre os idosos brasileiros (65-74 anos) e verificar fatores associados. Foram analisados dados de 7.496 idosos participantes do Pesquisa Nacional de Saúde Bucal realizado em 2010 (SBBrasil, 2010). O uso e a necessidade de prótese dentária foram usados como desfechos. As variáveis de exposição incluíram características demográficas, socioeconômicas, de uso de serviços e de autopercepção da saúde bucal. Análises descritiva, bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
30

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 26 publications
0
11
0
30
Order By: Relevance
“…Among the individuals who lost at least one tooth, this study showed lower prevalence of prostheses use in the segment of lower household income per capita in adults, and in the intermediate income segments in older adults. A study using SB-Brasil 2010 data did not find differences among the income segments regarding the use of prostheses in older adults 16 .…”
Section: Oral Conditionsmentioning
confidence: 91%
See 2 more Smart Citations
“…Among the individuals who lost at least one tooth, this study showed lower prevalence of prostheses use in the segment of lower household income per capita in adults, and in the intermediate income segments in older adults. A study using SB-Brasil 2010 data did not find differences among the income segments regarding the use of prostheses in older adults 16 .…”
Section: Oral Conditionsmentioning
confidence: 91%
“…Among the socioeconomic conditions, despite low income limiting access to hygiene products 13 , to dental services 14 and to knowledge about correct oral hygiene habits, leading to a higher prevalence and severity of dental caries 15 , few Brazilian studies have evaluated inequalities in oral health and the use of dental services between the different income strata at national level 9,[16][17][18][19][20] . Only two of these studies 18,20 used the income variable to analyze social inequalities in the access to and use of dental services.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Com a transição demográfica, proveniente do envelhecimento da população, bem como da redução da taxa de mortalidade e fecundidade, estima-se que no ano de 2020, o número de idosos no Brasil alcançará 32 milhões (AZEVEDO, et al 2017;ROSEDO, et al, 2017).…”
Section: Introductionunclassified
“…Sabe-se que fatores socioeconômicos, demográficos e relativos a padrão de uso de serviços influenciam o uso e a necessidade de prótese 24,25 . Houve diferença estatística em relação à necessidade de reabilitação protética inferior, acompanhada de um aumento da necessidade de prótese total inferior, para aqueles idosos que se tornaram edêntulos neste arco.…”
Section: Discussionunclassified